ANALYSIS OF THE ASSESSMENT OF THE LEVEL OF HEALTH OF NON-FINANCIAL SERVICES SOES BASED ON THE DECREE OF THE MINISTER OF SOES NUMBER: KEP-100/MBU/2002 - Handayani, Sri Wahyu; Rahmawati, Amelia (Universitas Gunadarma, 2024)
This research aims to determine the health level of non-financial services BUMNs in the tourism sector for the 2021-2022 period, assessed by each aspect, namely finance, operations and administration based on the Decree of the Minister of BUMN Number: KEP-100/MBU/2002. The analysis method uses quantitative methods with secondary data types, the object of this research is non-financial services state-owned companies in the tourism sector. The technique used in this research refers to the Decree of the Minister of BUMN Number: KEP-100/MBU/2002. The results of this research show that PT Hotel Indonesia and Natour in 2021-2022 received the Less Healthy category, PT Development Tourism Bali in 2021-2022 received the Unhealthy category, and PT Development Tourism Bali in 2021-2022 received the Healthy category.